Four seasons of Czech asthma study: asthma characteristics and management reality in the Czech Republic. (2nd August 2020) - Terl, Milan; Pohunek, Petr; Kuhn, Matyas; Bystron, Jaromir
Abstract: Objective: To describe the characteristics and management of asthma in clinical practice in the Czech Republic in the context of international guidelines and clinical realities. Methods: Data were collected over four seasons from summer 2016 to spring 2017 and are mostly presented using descriptive statistics. Results: We obtained valid data for 4557 adult patients with asthma, including detailed phenotyping (71% eosinophilic allergic, 10% eosinophilic non-allergic, 19% non-eosinophilic non-allergic asthma) from 58 allergologists and 56 pulmonologists. The average time to diagnosis was 3 years. In more than half of the subjects, bronchodilator testing (BDT) results were available at primary diagnosis. More than 10% of physicians did not test for mold allergy. Occupational asthma was diagnosed in 0.7% of subjects. According to the attending physician, 68% of patients had well-controlled and 10% had uncontrolled asthma. Ninety-four percent of patients were on preventive treatment, with 91% using an inhaled corticosteroids (ICS) at an average dose of 705 µg/day budesonide equivalent. Approximately 75% of patients were on an ICS/LABA, with 91% using fixed combinations. Among patients using ICS/formoterol, a maintenance and reliever therapy regime was prescribed in 67%. Conclusions: The quality of asthma management in the Czech Republic is comparable to that of other developed countries and better in some respects (frequent BDT, phenotyping, and use of preventive treatment). Nevertheless, there is unnecessary delay in diagnosis and lack of research on possible environmental causes (workplace, molds). Pharmacotherapy shows good adherence to guidelines. Although 10% of patients show poor control, there is concurrently a trend for overtreatment.